Walk7® - Rosilawati, Z. (University of Malaya, 2014)
Walk7 is a term used to refer to seven elements of walkability index. The elements include the quality of pathway, zebra crossing, street furniture, signage, and personal safety and adjacent to traffic flow and aesthetic and amenities. These seven elements are required to provide a comfortable walking condition at any place, especially in urban areas. Every element has several items that can be measured. All these elements must be present to provide a comfortable and high quality of walkability. 1) Pathway: type. width, capacity, condition, obstruction, connectivity, accessibility, design of footpath, quality, availability of alleys, availability of shade/covered walkway, availability of street furniture, sufficient lighting, disable friendly, child-friendly, elderly friendly, landscaping, maintenance level, and walkway environment. (2) Zebra crossing: type, location, accessibility, condition, availability of traffic light, function of traffic light, waiting time, length of crossing time and crossing safety. (3) Street Furniture: availability of street furniture, placement of lamp post, availability of sculpture, placement of sculpture, condition, and maintenance (4) Signage: availability of signage, placement of signage, availability of information board, condition, and maintenance (5) Personal safety: daytime, night time, comfortable personal space, comfortable social space, comfortable friendly space, fear of crime, fear of motorized vehicle and fear of stray animal (6) Adjacent to traffic flow: along the pedestrian walkway, pedestrian crossing and traffic control by authorities (7)Aesthetic and amenities: Aesthetic, availability of amenities, availability of dustbin, availability of public toilet, availability of benches and placement of benches